Evaluation of Online-Based Ride-Hailing Services Using Service Quality (Servqual) Method, Refined Kano Model, Importance Performance Analysis (IPA), and Quality Function Deployment (QFD): A Case Study of Grab Bike Indonesia - Dino Caesaron; Jessie Makapedua; Rio Prasetyo Lukodono (Bina Nusantara University, 2021)
The rapid development of the service industry in Indonesia is seen from the emergence of several companies in the transportation sector based on online applications. To compensate for the public needs of these services, the company needs to maintain customer satisfaction from the service performance. The research aimed to evaluate the quality of transportation services at Grab Bike Indonesia. By using quantitative and qualitative approach, the research applied Service Quality (Servqual) analysis for the level of perceived satisfaction, Refined Kano model for the role of each attribute to customer satisfaction, Importance Performance Analysis (IPA) for the priority of improvements, and Quality Function Deployment (QFD) for the technical steps of improvement. Servqual analysis shows 36 service attributes that need to be improved, particularly 16 service attributes with high gap scores. Furthermore, there are 5 attributes classified as major influencing attributes on customer satisfaction based on Refined Kano analysis. These factors also need to be improved in the IPA category. From the results of QFD, it suggests that the company should consider the technical steps of improvement. For example, the company should provide regulations that drivers must obey, have driving standards, strict sanctions for every violation of rules, initial training for drivers, and utilization of GPS properly, provide an easy way for customer feedback, and others.